Descriptive study evaluating the use of the Road to Health card by doctors in a tertiary paediatric hospital setting - Wiles, Jodi Isaacs (Department of Paediatrics and Child Health, 2016)
Background: The South African Road to Health Card (RTHC) is a parent-held personal child health record used by health professionals and parents to monitor the health and development of a child. Low possession and retention of the RTHC by parents, as well as inadequate use of RTHC by health professionals, have lessened its efficacy and purpose. Objectives: This study aimed to describe the level of possession of the RTHC by a sample of caregivers of patients admitted to Red Cross War Memorial Children's Hospital (RCWMCH), and to determine the extent and accuracy of doctors' transfer of clinical information between the RTHC and hospital records. Methods: A cross-sectional and analytical study was conducted in four general paediatric wards at RCWMCH. Consecutive patients were enrolled at discharge during office hours over a six week period. Data were extracted from a photograph of the RTHC and the participant's hospital record. Both the 1995 Chart version and the 2009 Booklet version of the RTHC were included in the study. The presence or absence of selected items of information on the RTHC and the hospital record were recorded - the primary outcome was the transfer of the specified information between records. The outcomes are presented as proportions, with 95% confidence intervals (CI).